Bodies, Bollywood and Bond. The evolving image of secret agents in Hindi spy thrillers inspired by the 007 franchise - Lipka-Chudzik, Krzysztof (Acta Orientalia Vilnensia, 2011)
Independent researcher In the 1960s, after the international commercial success of the James Bond films, many imitations and parodies of the original were made in different parts of the world. In India popular Hindi films were also inspired by the 007 franchise, beginning with the action thriller Farz in 1967. From then on a new genre was formed in the Bombay cinema: Hindi Bond films. These derivative productions were deliberately created to replicate the plot formula and narrative structure of the original Bond series. They underwent considerable development from cheap, amateurish B-movies to big budget commercial hits such as Ek Tha Tiger in 2012. Also the leading characters in Hindi Bond films, the secret agents of the Indian police and intelligence, evolved from the innocent, happy-go-lucky youngsters in the 1960s into the tough, world-weary men of action in the 2010s. One of the most important factors of this gradual change is the way the heroes’ bodies were shown on screen. The focus on the esthetics, the musculature, the physical abilities and sex appeal of the Bombay Bonds was different in every decade. This article concentrates on the evolution of Hindi Bond films: the genre as well as the leading characters.